Methodological Development of a Combined Preparation for Micropaleontological and Sedimentological Studies of Samples From the Proterozoic Record - Denezine, Matheus; Adôrno, Rodrigo Rodrigues; Do Carmo, Dermeval Aparecido; Guimarães, Edi Mendes; Walde, Detlef Hans Gert; De Alvarenga, Carlos José Souza; Germs, Gerard; Antonietto, Lucas Silveira; Valdivia Rodríguez, Christian Gianfranco; Nunes Junior, Osvaldo De Oliveira (Frontiers in Earth Science, 2022)
The recovery of microfossils from Proterozoic rocks is commonly challenging because of metamorphism. In this study, an application of different methods usually applied on Phanerozoic rocks to test efficiency on recovering microfossil from Proterozoic units is presented. Chemical, physical, and biological factors can influence the recovery of microfossils, thereby becoming a barrier for biostratigraphic and paleoecological studies. Furthermore, low-cost projects with a reduced amount of sample collected, such as drill core sampling, need to optimize the preparation time and sample needed for different analyses. To overcome this challenge, the classical procedure of mineralized microfossil preparation, the palynological technique, and the study of clay mineralogy with the analyses of diagenetic alteration and the search for possible microfossils in thin sections were combined. Three Proterozoic lithostratigraphic units were selected to develop an integrated procedure for preparing samples for micropaleontologic and sedimentologic studies: the Paranoá Group, Mesoproterozoic, and the Bambuí Group, Ediacarian-Cambrian, Brazil, and Nama Group, Ediacaran-Cambrian, Namibia. Recovering individual microfossils from the Paranoá and Bambuí groups has been a challenge for paleontologists. Therefore, most micropaleontological studies have been done as a part of microbiofacies analyses in thin sections. All sediment fractions were studied in trial for the examination (and picking) of mineralized microfossils, even the finest ones. The microfossil picking was conducted using a stereomicroscope. Three species were recovered following this procedure: Vetronostocale aff V. amoenumSchopf and Blacic, 1971, Myxococcoides sp., and Melanocyrillium sp. Analyses in whole rock samples of residues from water (H2O) and hydrogen peroxide 30% (H2O2) procedures showed similar results when the clay fraction studied was obtained as part of micropaleontological preparation compared with the results from the standard clay mineral preparation method. The clay fraction diffractograms showed that the micropaleontological preparation with H2O and H2O2 caused an increase in the intensity of the quartz reflections compared with untreated samples. Moreover, detailed protocols for organic-walled microfossil preparation and low concentrated acetic and formic acids attacks for mineralized microfossil extraction were presented.